2020
DOI: 10.1038/s41598-020-63744-8
|View full text |Cite
|
Sign up to set email alerts
|

The Liver and Kidneys mediate clearance of cardiac troponin in the rat

Abstract: Cardiac-specific troponins (cTn), troponin T (cTnT) and troponin I (cTnI) are diagnostic biomarkers when myocardial infarction is suspected. Despite its clinical importance it is still not known how cTn is cleared once it is released from damaged cardiac cells. The aim of this study was to examine the clearance of cTn in the rat. A cTn preparation from pig heart was labeled with fluorescent dye or fluorine 18 (18 F). The accumulation of the fluorescence signal using organ extracts, or the 18 F signal using pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…1) In cells of the reticuloendothelial system (intracellular cleavage by specific proteases); 93 , 94 …”
Section: Cardiac Troponins In Chronic Renal Failure: Mechanisms Of Elevation and Diagnostic Valuementioning
confidence: 99%
“…1) In cells of the reticuloendothelial system (intracellular cleavage by specific proteases); 93 , 94 …”
Section: Cardiac Troponins In Chronic Renal Failure: Mechanisms Of Elevation and Diagnostic Valuementioning
confidence: 99%
“…They observed an increase in prevalence of participants with troponin concentrations over the 99th percentile from 1 to 9% after walking. During an average of 43 [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] months of follow up, patients with acute myocardial injury had a significantly increased risk of all-cause mortality or...…”
Section: Mechanisms Of Myocardial Injurymentioning
confidence: 99%
“…This can likely be explained by scavenger receptors having reduced affinity for troponin at such low concentrations and smaller degradation products of troponin readily passing through the glomerular membrane. A further study using radiolabelled cardiac troponin in rats revealed uptake in both the kidneys and liver, with liver uptake inhibited through inhibition of endocytosis, suggesting both renal and extra-renal systems of clearance [ 74 ]. These studies may explain the correlation between those with reduced renal function and slightly elevated concentrations of circulating cardiac troponin.…”
Section: Mechanisms Of Myocardial Injurymentioning
confidence: 99%
“…Similarly, Brown et al showed that the use of hs‐TnT compared to conventional TnT increased the detection rate of MINS by a factor of 2 24 . One could argue that the increase in hs‐TnT post‐operatively could to some extent be caused by an impairment of renal function, as there was a positive correlation between serum creatinine and hs‐TnT and as circulating hs‐TnT is cleared from plasma by renal filtration and hepatic clearance 25 . The role of perioperative kidney dysfunction to explain the perioperative release of hs‐TnT in major surgery has, to our knowledge, not been addressed previously, which should be done in larger cohorts of patients undergoing high‐risk surgery.…”
Section: Discussionmentioning
confidence: 99%